Evaluation of Water Quality Using Water Quality Index (WQI) Method and GIS in Al-Gharraf River Southren of Iraq - Wisam Thamer Al-Mayah (Journal of Global Pharma Technology, 2018)
Abstract: The present study describes the application of Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) for for twenty-one stations along the Al-Gharraf River from  Kut Dam when the river branching from Tigris to its end in the northern of Nassiria city. Sixteen water quality parameters under investigation were as follows: WT (9–33°C), pH (6.51–8.25), NTU (11–157), EC (700–1652 μS/cm), TDS (448–1057.23 mg/l), TSS (23–194 mg/l), DO (3.42–10.8 mg/l), BOD5 (0.79–9.07 mg/l), TH (218–689 mg/l), CL (87–381.3 mg/l), SO4 (111.8–469 mg/l), NO3 (3.01–33 mg/l), PO4 (0.107–0.964 mg/l), Pb (0.007–0.242 ppm), FC (180–97000 cfu/100ml) and CHL-a (0.033–9.534 mg/l). were used during the period from December, 2016 to November, 2017.Based on the results of this application, the general surface water quality in the Al-Gharraf River is found to be not suitable for use as drinking water without elaborate treatment, poor for aquatic life protection and fair for irrigation.Keywords: CCME WQI, GIS , Water quality, Al-Gharraf River.